Analisis Kebijakan Kewirausahaan Nasional Di Metaverse - Abdurrofi Abdullah Azzam (Jurnal Administrasi dan Kebijakan Publik, 2022)
Metaverse as a digital phenomenon has had an impact on global life since the Covid-19 pandemic took place. Almost all countries experienced disruption in various sectors. One of the countries undergoing transformation is Indonesia. This transformation has become an attraction for researchers to examine the steps taken by the Indonesian government to address the demand for national entrepreneurship in the Metaverse. Moreover, the metaverse has both opportunities and challenges. This study focuses on the public policy dimensions of the Indonesian government in dealing with national entrepreneurship and aims to analyze the factors that play a role in the effectiveness of implementing public policies in the use of the metaverse in Indonesia by using the policy implementation model offered by the Brian W. Hoogwood and Lewis A model. Guns. This study uses qualitative research methods with data collection by literature study. The results show that Indonesia has not optimally developed a national entrepreneurship policy in the metaverse.